Hegemonic Masculinity Aspect On Otto Anderson’s In The Film “A Man Called Otto” - I Pande Putu Kenzie Arvan Nismara; Mulyana, Novita; Netra , I Made (Denpasar Institute, 2025)
This research, entitled Hegemonic Masculinity in Otto Anderson’s Character in A Man Called Otto, aims to examine the representation of hegemonic masculinity through Otto Anderson's character and explain the cultural factors that contribute to its construction. The primary data were drawn from the 2022 film A Man Called Otto, focusing on utterances that reflect traits associated with hegemonic masculinity. The data were collected using documentation and systematic note- taking techniques and were analyzed through a descriptive qualitative method. Connell’s (2005) theory of hegemonic masculinity and Wharton’s (2005) cultural framework were applied to investigate how masculinity is constructed and performed. The findings revealed a total of 154 utterances categorized into four aspects of hegemonic masculinity: emotional suppression, aggression, competitiveness, and power. These findings demonstrate that Otto’s behavior reflects socially constructed masculine norms shaped by cultural and generational values. The analysis further shows that masculinity is not an inherent trait but a performative identity regulated by social institutions. The study concludes that contemporary media, as exemplified in this film, plays a significant role in reinforcing and challenging hegemonic masculinity through character development and narrative structure.